PHYSICOCHEMICAL CHARACTERIZATION OF THE LULO (Solanum quitoense Lam.) CASTILLA VARIETY IN SIX RIPENING STAGES - Mejía D. M.Sc., Clara María; Gaviria A. Ph.D., Duverney; DUQUE C. M.Sc., Alba Lucia; RENGIFO R. M.Sc., Lucero; AGUILAR F. B.Sc., Enrique; ALEGRÍA S. Ph.D., Alvaro Hernan (Vitae, 2012)
Background: Lulo (Solanum quitoense Lam) is considered a fruit with a high potential for exportation due to its exotic aroma, its bittersweet taste and the bright green color of its pulp. As a climacteric fruit is harvested when the fruit has reached full development, and 75% of the ripening is apparent by its characteristic yellow color with some small green points. However, this parameter is not enough to decide the right time for the crop, due to the irregularity of the fruits, especially for selling purposes in international markets, hence studies have been conducted to establish the changes during ripening and postharvest. Objectives: The aim of this work was to determine the relationship between color measurement and the other physicochemical parameters in the six ripening stages of lulo Castilla variety, in order to define the optimal harvesting time. Methods: Three fruits were studied for each stage, and were analyzed in the fresh state: ° Brix, pH, titratable acidity and color changes in the cortex, according to CIELab system. Results: The ranges obtained for the six evaluated stages were: ° Brix: 4.2 - 10.3, pH: 3.67 - 3.90, acidity: 2.63 - 3.00 and color (ΔE): 0 - 53. We found that the epicarp of the fruit varies from green to yellow intense, indicating the maturity for consumption. Total soluble solids increased with fruit maturation and the tritatable acidity decreased reaching a minimum values at stage 3, which was considered optimum for harvesting. The pH increased in stage 5 due to the drop of vacuolar H+ ion concentration. Conclusion: By measuring color parameters, 3 ripening stages were defined: green (0, 1, 2); semi ripe (3, 4) and ripe (5).